Mengintegrasikan Asesmen Formatif di Sekolah Dasar: Sebuah Tinjauan Sistematis terhadap Landasan Filosofis, Implementasi, dan Dampak Holistik: Abstract, Pendahuluan, Metode, hasil dan pembahasan, kesimpulan, daftar rujukan - Khairatunnisa, Aulia; Ayumi NA, Afdal; Wulan safitri, Lenggana; Meisya Putri, Nadya; Muhammadi (Journal of Practice Learning and Educational Development, 2026)
This article presents a systematic review of recent empirical research on the implementation of formative assessment in elementary schools 2020-2025. Formative assessment is defined as the ongoing process of collecting and using evidence of learning to guide instruction and improve student achievement (assessment for learning). Following the PRISMA protocol, researchers identified 38 studies from 512 articles found through searches in indexed databases. A thematic analysis of these studies revealed three main themes: (1) the conceptual evolution from evaluation techniques to a pedagogical philosophy based on dialogue and student agency; (2) the complexity of implementation related to socio-emotional dynamics, cultural contextualization, and technology integration; and (3) multidimensional impacts on academic achievement, 21st-century competencies, and teacher professional identity. Successful implementation depends on teachers' ability to create psychologically safe spaces, build reflective dialogue, and design responsive systems. The conclusion states that effective implementation requires a systemic approach through continuous professional development, instructional leadership, and supportive policies. Future research is recommended to adopt participatory design, develop contextual frameworks, and expand studies on the affective-spiritual dimensions of formative assessment.